2019
DOI: 10.33321/cdi.2019.43.30
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination coverage in a population-based cohort of Australian-born Aboriginal and non-Indigenous older adults

Abstract: Background: There is limited information on vaccination coverage and characteristics associated with vaccine uptake in Aboriginal and/or Torres Strait Islander adults. We aimed to provide more current estimates of influenza vaccination coverage in Aboriginal adults. Methods: Self-reported vaccination status (n=559 Aboriginal and/or Torres Strait Islander participants, n=80,655 non-Indigenous participants) from the 45 and Up Study, a large cohort of adults aged 45 years or older, was used to compare influenza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Information about vaccination status of the participants was unavailable. Evidence [39], suggests that in uenza vaccination reduces cardiovascular events and mortality and it is possible that vaccination may have impacted mortality in this study as annual in uenza vaccination coverage in adults in Australia is 54% [40].…”
Section: Discussionmentioning
confidence: 84%
“…Information about vaccination status of the participants was unavailable. Evidence [39], suggests that in uenza vaccination reduces cardiovascular events and mortality and it is possible that vaccination may have impacted mortality in this study as annual in uenza vaccination coverage in adults in Australia is 54% [40].…”
Section: Discussionmentioning
confidence: 84%
“…Information about vaccination status of the participants was unavailable. Evidence [38], suggests that influenza vaccination reduces cardiovascular events and mortality and it is possible that vaccination may have impacted mortality in this study as annual influenza vaccination coverage in adults in Australia is 54% [39].…”
Section: Discussionmentioning
confidence: 84%
“…Use of clinical and public health interventions may vary by both First Nations status as well as by location. This is evident with higher uptake of seasonal influenza immunisation amongst First Nations populations compared to non-Indigenous populations, although coverage is still sub-optimal (41,42). No study reported on use of non-pharmaceutical interventions, such as isolation.…”
Section: Discussionmentioning
confidence: 99%